MUTU ORGANOLEPTIK COOKIES DENGAN PENAMBAHAN TEPUNG BEKATUL DAN IKAN KEMBUNG - Nadimin Nadimin; Sirajuddin Sirajuddin; Nuraliah Fitriani (Media Gizi Pangan, 2019)
Additional food should use inexpensive and reasonably-available local foodstuffs such as bran and mackerel. Bekatul has a nutrient producing nutrients that are high enough but not yet utilized optimally. While bloating is an essential source of protein and fatty acids that are essential for growth. This research aims to determine the quality of organoleptik Cookies add starch and pufferfish.Research using the design of group comparison design, comparing the quality of the original including Cookies (F1) and cookies replenishment of rice bran and pufferfish (F2). Organoleptik quality is assessed sensory based on the favorite level of panelist against the color, texture, aroma and flavor aspects. The favorite level is made in six levels ranging from dislikes to very very fond (score 1-6). Data analysis using the Mann Whitney U test.Panelis who liked the color of cookies F1 62.9% and cookies F2 57.1%, liked the texture of cookies F1 65.7% and cookies F2 65.7%. Panelist who likes to aroma cookies F1 85.7% and cookies F2 54.3% and likes to taste cookies F1 82.9% and cookies F2 62.9%. There is no quality difference organoleptik between the F1 cookies and cookies F2 of the color aspects (P = 0,511) and texture (P = 0,787). There is a significant difference in the quality of organoleptik between the F1 cookies and cookies F2 from the aroma aspect (P = 0,003) and flavor (P = 0,013). U.Addition of rice bran and mackerel does not affect the quality of organoleptik from the color and tektur aspects, but can reduce the quality of organoleptik from the aroma and color aspects of cookies. It is necessary to reduce the concentration of bloated fish flour and add other ingredients that can mask the aroma and flavor of fish.